2021
DOI: 10.3390/chemosensors9080202
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dots from Lemon Waste Enable Communication among Biodevices

Abstract: A bioinspired method of communication among biodevices based on fluorescent nanoparticles is herein presented. This approach does not use electromagnetic waves but rather the exchange of chemical systems—a method known as molecular communication. The example outlined was based on the fluorescence properties of carbon dots and follows a circular economy approach as the method involves preparation from the juice of lemon waste. The synthesis is herein presented, and the fluorescence properties and diffusion coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…4a were obtained by changing the flow velocity and keeping constant the diffusion coefficient having a value of 3 × 10 −10 m 2 /s. This value was chosen based on information nanoparticles with a typical size of about 2 nm [38]. It can be observed that none of the signals in question have a Gaussian distribution but are all curves with distorted symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…4a were obtained by changing the flow velocity and keeping constant the diffusion coefficient having a value of 3 × 10 −10 m 2 /s. This value was chosen based on information nanoparticles with a typical size of about 2 nm [38]. It can be observed that none of the signals in question have a Gaussian distribution but are all curves with distorted symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 The raw materials used vary widely, ranging from simple carbonaceous sources such as citric acid 24 and simple carbohydrates 25 to polymers 26 including biopolymers, 27 and even biomass and food waste. 28 CNPs exhibit optical absorption peaks primarily in the UV region and partly in the visible. The transitions are generally associated with the p-p* transition of the sp2 conjugated carbon and the n-p* transition of hybridization with heteroatoms of the outer shell containing carboxyl groups or associated with the presence of N, S, P, etc.…”
Section: Manuelamariamentioning
confidence: 99%
“…22,23 The raw materials used vary widely, ranging from simple carbonaceous sources such as citric acid 24 and simple carbohydrates 25 to polymers 26 including biopolymers, 27 and even biomass and food waste. 28…”
Section: Introductionmentioning
confidence: 99%
“…The formation of these nanoparticles in soot from candles, coffee grounds, milk or burnt hair has been confirmed [11] Since their first discovery in 2004 [12] , the potential of carbon-based CQD was immediately clear, and in the years that followied the scientific community produced a large amount of literature reporting many synthetic techniques with different levels of sophistication. These included laser ablation processes, pyrolysis, hydrothermal synthesis, microwave-assisted synthesis, and electrochemistry [ 13 , 14 ] starting from any organic carbon-based raw material, including food waste [15] . Structurally, these CQD appear as discs/spheres with diameters ranging from ∼2–30 nm.…”
Section: Information Nanoparticlesmentioning
confidence: 99%